Constructing a Framework of PKTL Decision Support System Design - Sukoharsono, Eko Ganis (Accounting Department,, 2025)
Purpose — This study aims to analyze the development of young farmers in UB Forest as woodcraft souvenir producers by implementing a sustainable accounting model based on the pentuple bottom line. The study investigates the social, environmental, economic, technological, and spiritual dimensions influencing community empowerment and craft production. Design/methodology/approach — Using a participatory method involving the community and youth around UB Forest, data were collected through observations, training activities, and stakeholder engagement. The model applies the pentuple bottom line framework covering people (social), planet (environment), profit (economic), pheno-technology (technology), and prophet (spiritual) aspects. Findings — The study finds significant improvements in skills and awareness among the community and youth, sustainable use of natural resources, and increased income through woodcraft sales. Technological applications are in early stages with plans for modernization, while spiritual education supports the community’s resilience and values. The holistic approach fosters sustainable development compatible with environmental conservation and community welfare. Practical implications — This integrated accounting model empowers local communities by enhancing socio-economic welfare, preserving biodiversity, and promoting spiritual growth. The model provides a replicable framework for sustainable community development in natural resource-based industries, emphasizing the importance of multidimensional sustainability. Originality/value — This case presents a comprehensive application of the pentuple bottom line in community service, illustrating sustainability accounting beyond traditional financial metrics. It contributes novel insights into sustainable rural development linking spirituality with economic and environmental aspects in an emerging economy context.